-8(-3m-3)-7m=

Simple and best practice solution for -8(-3m-3)-7m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(-3m-3)-7m= equation:


Simplifying
-8(-3m + -3) + -7m = 0

Reorder the terms:
-8(-3 + -3m) + -7m = 0
(-3 * -8 + -3m * -8) + -7m = 0
(24 + 24m) + -7m = 0

Combine like terms: 24m + -7m = 17m
24 + 17m = 0

Solving
24 + 17m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 17m = 0 + -24

Combine like terms: 24 + -24 = 0
0 + 17m = 0 + -24
17m = 0 + -24

Combine like terms: 0 + -24 = -24
17m = -24

Divide each side by '17'.
m = -1.411764706

Simplifying
m = -1.411764706

See similar equations:

| m/n=7.3 | | 30=7(y-5)+6 | | 2(3x+5)=76 | | 12(5+2y)=4y-(6-8y) | | -18=c-5 | | -2(7x+1)=14-6x | | 200=xl | | x=35313(35313*0.16) | | 6z+7=5z+6 | | 400/460 | | m-(-18)=7 | | -5x-4-5x=-24 | | 7-3y+6=-7 | | 9=5+2g | | -4(6n-4)-7= | | ax^2-bx^2=0 | | 16+c=-5 | | 1+4a-a= | | 15y+3x=61 | | 0=-16t^2+24t+40 | | 4+2q=8 | | 5n+3=4-6(6-5n) | | p+(-9)=8 | | 10=3y+1 | | -14-8k=2k+8k | | 3x=x^2+9 | | 50=x(x*0.16) | | -12+5m+10=2m-10-m | | (15/28)/35 | | t/7=-9/1 | | 8r-5q=3forq | | -d+7= |

Equations solver categories